La educación de la ciudadanía: una propuesta de «solidaridad y sentido» - Fernández, Fernando Vidal (Miscelánea Comillas, 2005)
The paper develops the contents of the area of solidarity and sense in the school. First, it sets the links between solidarity and sense; second, it analyzes the structure of the culture for knowing which must be the pedagogical conditions of the teaching of the solidarity and the sense and which is the institutional frame since a sense formed by a quadruple figure of truth, good, beauty and praxis. This complex sense is narrated by the imaginary, which is a system of icons. That structure of the culture justifies that the formation must be historical and narrative and must help to relate, to link, to choice and to experiment every content. At least, the paper describes a curricular proposal called Solidarity and Sense. The paper defends that this approach and this curricular structure are able to get a solution at the educational and political debate about religion, ethic and citizenship.